Communicating risk under high uncertainty: developing cross-disciplinary knowledge - Wardman, Jamie; Mythen, Gabe (Taylor & Francis, 2016)
The primary purpose of this Special Issue is to coalesce different perspectives on the theme of ‘Communicating Risk Under High Uncertainty’ from across a range of subject areas. These areas include environmental studies, international relations, engineering, sociology, psychology, media studies, the health sciences, criminology and anthropology. By bringing different perspectives together, we anticipate that commonalities and points of concurrence will help to identify cross-disciplinary synergies and provide opportunities to explore the potential for a more holistic understanding of risk communication in the academy and beyond.